The Pivotal Role of Ponderal Effect on the Energetics of Tertiary Amine/quaternary Ammonium Systems in Aliphatic Alcohols - Jessy, J.M. (Asian Journal of Chemistry, 2010)
A comparative study has been made of the reactivities of five closely related reactions, involving tertiary amines and/or quaternary ammonium salts in aliphatic alcohols. The qualitative and quantitative effects of changing alkyl substitution in the alcohols (along the series) on the transition or activation energies of the reactions were compared, for the sake of mechanistic details of solvation which could be obtained therefrom. The results nistic details of solvation which could be obtained thereform. The results demonstrate the surprising significance of ponderal hindrance in solvation—which is shown, in one of the reactions, to have reversed the direction of the relative reaction rates anticipated on the basis of polar factors alone.